Concentration of Children's Learning in Motor-Sensory Play Management Development Framework - Chusnul Mualli; Moh. Rofiki; Feriska Listrianti; Miri Jufria Vinori; Muhaiminah Muhaiminah (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
In growing a child's concentration level, an appropriate method is needed to stimulate more stable focus and concentration. This study aims to examine efforts to increase children's learning concentration by managing sensory-motor play in early childhood, which is carried out at an institution under the auspices of the Nusus Salam Foundation, namely RA Nurus Salam. The research method uses a qualitative case study approach. To get an idea of the Efforts to Increase Children's Learning Concentration Through Sensory Motor Play Management, the researcher went directly to the institution and observed the RA Nurus Salam institution by interviewing the principal and three teachers. The results showed that; The RA Nurus Salam institution uses the management of sensory-motor play to stimulate the increase in children's learning concentration and the involvement of teachers' strategies in the direction of sensory-motor play using; first, lesson planning. Second, implementation of learning design, and third, evaluation. The implication is that children's concentration and focus are more stable when carrying out activities with sensory-motor management.